Gambaran Risiko Kematian Pasien Terkonfirmasi COVID-19 di Rumah Sakit Bethesda: Analisis Skor Mortalitas 4C - Vallentino Ardine Prasetya Bisay; Rizaldy Taslim Pinzon; Esdras Ardi Pramudita (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: The high incidence of death in patients with COVID-19 requires a risk stratification tool to assess the patient's condition and determine appropriate medical action. The 4C mortality score is a stratification tool that uses patient demographics, clinical observations and laboratory parameters to describe the patient's risk of death. Method: This study used a nested case-control method with secondary data on patients with confirmed COVID-19. The sample with 71 confirmed COVID-19 patients was categorized into groups of patients who died (cases) and patients who recovered (controls). Data analysis using the independent T test and bivariate using the chi-square method to see the relationship between the 4C mortality score and the incidence of patient death.Results: It was found that the 4C mortality score in the group of patients who died was higher compared to patients who recovered (mean = 8.20 vs 4.05). A significant relationship was found between the 4C mortality score and the incidence of death in COVID-19 patients (OR = 22.696; 95% CI = 2.82-182.9; p = 0.0034)Conclusion: It can be concluded that the 4C mortality score of medium and high COVID-19 patients is associated with the risk of patient death.